Torsional Vibration of a System with a Friction Clutch Under Random Torque Excitation - W. Kurnik; Z. Skup (Engineering Transactions)
The paper presents a theoretical study of torsional vibration in a two-mass model of a transmission system with a multi-disc flexible friction clutch under random excitation. Energy is dissipated through micro-slip processes between discs, characterized by a hysteresis loop. It is assumed that the nominal driving torque is disturbed by a stationary Gaussian random excitation with known moments. Spectral density as well as the mean value and standard deviation of both the relative torsional vibration and the driven part vibration are derived using a stochastic linearization technique applicable in hysteretic systems. The role of system parameters is shown by examples in which a band model of random excitation is assumed.